2016
DOI: 10.1038/nm.4181
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of acetyl-CoA carboxylase suppresses fatty acid synthesis and tumor growth of non-small-cell lung cancer in preclinical models

Abstract: Continuous de novo fatty acid synthesis is a common feature of cancer required to meet the biosynthetic demands of a growing tumor. This process is controlled by the rate-limiting enzyme acetyl-CoA carboxylase (ACC), an attractive but traditionally intractable drug target. Here, we provide genetic and pharmacological evidence that in preclinical models ACC is required to maintain de novo fatty acid synthesis needed for growth and viability of non-small cell lung cancer (NSCLC). We describe the ability of ND-64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
326
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 392 publications
(361 citation statements)
references
References 42 publications
13
326
0
3
Order By: Relevance
“…Among them, several molecules against ACC have been developed. 21 In a recent study, it was shown that ND-646, an allosteric ACC1/2 inhibitor, suppresses tumor growth in both xenograft and genetic engineered mouse models of non-small cell lung cancer, either alone or in combination with standard-of-care drug carboplatin, 53 supporting the further testing of ACC inhibitors for cancer treatment.…”
Section: Fasn Is Required For Akt and Akt/c-met Driven Hepatocarcinogmentioning
confidence: 98%
“…Among them, several molecules against ACC have been developed. 21 In a recent study, it was shown that ND-646, an allosteric ACC1/2 inhibitor, suppresses tumor growth in both xenograft and genetic engineered mouse models of non-small cell lung cancer, either alone or in combination with standard-of-care drug carboplatin, 53 supporting the further testing of ACC inhibitors for cancer treatment.…”
Section: Fasn Is Required For Akt and Akt/c-met Driven Hepatocarcinogmentioning
confidence: 98%
“…Anti-cancer target discovery is one of the most promising translational applications for SIRM, and inhibitors of several targets have been developed and are showing promise in preclinical models (81). These inhibitors can also potentiate the efficacy of conventional chemotherapeutics (82).…”
Section: Applications Of Sirm In Drug Developmentmentioning
confidence: 99%
“…These data are in agreement with previous studies indicating that hepatocytes (Dzamko et al ., 2010) and macrophages (Fullerton et al ., 2015) from AMPK β1‐deficient mice have increased lipid synthesis and that activation of AMPK using A769662 or metformin lowers lipogenesis through an AMPK β1‐dependent pathway requiring the phosphorylation of ACC (Fullerton et al ., 2013). These data are also consistent with recent studies indicating that inhibiting lipogenesis, by mimicking AMPK phosphorylation of ACC using small molecules (Svensson et al ., 2016) or through chemical inhibition of fatty acid synthase (Menendez and Lupu, 2007; Orita et al ., 2008), is effective for limiting cellular proliferation. However, it is possible that the inhibition of proliferation is not directly related to the blunting of lipid synthesis but rather a buildup of malonyl‐CoA or some other metabolite.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in fatty acid synthesis are required to sustain rapid proliferation in many types of cancer [for review, see (Hanahan and Weinberg, 2011; Hirschey et al ., 2015)] including prostate and non‐small‐cell lung cancer (NSCLC) (Shah et al ., 2016; Svensson et al ., 2016; Villani et al ., 2016). Rates of fatty acid synthesis are governed by the expression of ATP‐citrate lyase (ACLY), acetyl‐CoA carboxylase (ACC), and fatty acid synthase (FAS) (Hanahan and Weinberg, 2011; Hirschey et al ., 2015; Shah et al ., 2016; Svensson et al ., 2016; Villani et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation